Review of the genus Anipocregyes Breuning, 1939 with two new species from Borneo (Coleoptera, Cerambycidae, Lamiinae, Mesosini) - Yamasako, Junsuke; Makihara, Hiroshi (Zootaxa, 2017)
The genus Anipocregyes Breuning, 1939 is reviewed. Cristipocregyes rondoni Breuning, 1965, Metipocregyes rondoni Breuning, 1965, and Mesosa (Perimesosa) seminivea Breuning, 1965 are transferred to the genus Anipocregyes, and Setomesosa rondoni Breuning, 1968 is synonymized with A. seminivea comb. nov. As a result, two genera, Cristipocregyes Breuning, 1965 and Setomesosa Breuning, 1968, are synonymized with Anipocregyes. Metipocregyes rondoni Breuning, 1965 becomes a secondary homonym and Anipocregyes albifrons nom. nov. is proposed as a replacement name. Anipocregyes kawakamii sp. nov. and A. wakabayashii sp. nov. are described from Borneo. All the seven known species of Anipocregyes are illustrated with their male genitalia (except for A. laosensis) and a key to the species is provided.